Oligo-carrageenan kappa, oligo-ulvans and carrageenan kappa differentially increase the level of hormones involved in growth and defense against biotic and abiotic stresses in Arabidopsis thaliana - (:unkn) unknown (ELSEVIER, 2026)
Arabidopsis thaliana plants were treated on leaves with an aqueous solution of oligo-carrageenan kappa (OCK), oligo-ulvans (OU) and carrageenan kappa (CK) at a concentration of 1 mg mL-1, five times, every two days, 15 d after germination (ag) and samples were collected at 20 d and 30 d ag. Phytohormones involved in the stimulation of growth such as the auxins indole-3-acetic acid (IAA) and indole-3-butyric acid (IBA), the gibberellins A3, A4 and A7, the cytokinins isopentenyl adenine (iP) and trans-zeatin (tZ), and the brassinosteroids castasterone (CAS) and epibrassinolide (eBL) were detected. Results indicate that OCK, OU and CK increased IAA level, mainly OCK; OCK increased GA3 level, OCK and OU increased GA4 and GA7 levels, but not CK; OCK increased iP level and OCK and OU increased in tZ level, but not CK, and OCK and OU increased eBL level, but not CK. Thus, OCK and OU increased growth-promoting hormones such as AUXs, GAs, CKs and BRs levels in A. thaliana. On the other hand, hormones involved in biotic and abiotic stress tolerance such as abscisic acid (ABA), 1-aminocyclopropane-1-carboxylic (ACC), castasterone (CAS), jasmonates and salicylates were detected. OCK increased ABA level; OCK and OU increased ACC levels and OU increased CAS level; OCK increased JA level, OCK and OU increased JA-ile level, OCK, OU and CK increased MeJA level; OCK, OU and CK increased SA level and OCK, OU and CK increased MeSA level. Thus, OCK increased ABA level suggesting that tolerance against drought may be enhanced; OCK and OU increased ACC, JA, JA-ile, MeJA, SA and MeSA suggesting that defense against pathogens and abiotic stress may also be increased. Therefore, OCK, OU and CK differentially stimulate growth and defense against biotic and abiotic stresses in A. thaliana.